A Review of : Mauro, Chiara Maria, Chapinal-Heras, Diego, and Valdés Guía, Miriam (eds.) 2022. People on the Move Across the Greek World. Sevilla: Editorial Universidad de Sevilla. - Thomsen, Christian Ammitzbøll (Pnyx: Journal of Classical Studies, 2023)
This is a review of the edited volume People on the Move Across the Greek World, edited by Chiara Maria Mauro, Diego Chapinal-Heras and Miriam Valdés Guía and published in 2022 by the Editorial Universidad de Sevilla (Seville University Press).